Does incorporating collagen and chondroitin sulfate matrix in implant surfaces enhance osseointegration? A systematic review and meta-analysis. Issue 2 (February 2018) - Kellesarian, S.V.; Malignaggi, V.R.; Kellesarian, T.V.; Bashir Ahmed, H.; Javed, F.
Abstract: Implant surface modification has been used to improve osseointegration. However, evidence regarding improved new bone formation (NBF) and osseointegration with the use of collagen–chondroitin sulfate (CS) matrix coated implants remains unclear. The aim of this study was to assess the efficacy of collagen–CS matrix coating on the osseointegration of implants. The focused question was "Does the incorporation of collagen–CS matrix in implant surfaces influence osseointegration?" To answer the question, indexed databases were searched up to July 2017 using various combinations of the key words "collagen", "chondroitin sulfate", "osseointegration", and "implants". The initial literature search identified 497 articles, of which 18 reporting experimental studies fulfilled the inclusion criteria. Thirteen of the studies included (72%) reported that implants coated with a collagen–CS matrix presented higher NBF, bone-to-implant contact, and/or bone volume density. The strength of this observation was supported by meta-analysis results. Nevertheless, the results should be interpreted with caution due to the lack of standardization regarding the dosage formulation of collagen–CS, short-term follow-up, and lack of assessment of confounders. On experimental grounds, the incorporation of collagen–CS matrix into implant surfaces appears to promote osseointegration. From a clinical perspective, the results from animal models support phase I studies in healthy humans.